Review Article: Physiological and Immune Alterations in Atherosclerosis: From Endothelial Dysfunction to Chronic Inflammation - Ahmed, Tamarah H.; Al-Mousawi , Noor H. (American Journal of Biology and Natural Sciences, 2025)
Atherosclerosis is an arterial wall disorder which is a chronic and progressive disease and has interrelations immunological and physiological events. The endothelium begins to malfunction and initiate a cascade of metabolic and biomechanical alterations, including a reduction in the bioavailability of nitric oxide, oxidative stress, and the lipoprotein retention of the intima. Also, recruitment and polarization of innate and adaptive immune cells are then increased, which increases inflammation, foam-cell generation, as well as, remodeling of the extracellular matrix, eventually causing plaque and instability. The recent discoveries (2019-2025) in vascular physiology and immunology, relevant to atherogenesis, are outlined in this review, which takes into consideration the understanding of endothelial shear stress, cholesterol handling, cytokine network, also, clonal hematopoiesis of unknown potential. As well as, clinical implications are also discussed with respect to the development of biomarkers and treatment strategies that focus on lipids, inflammation, and thrombosis, and new biological agents. Although, an appreciation of the interplay between physiological pathways and immunological circuits gives an integrative framework that can prevent the development of atherosclerotic cardiovascular events by stopping the formation of a plaque, promoting stabilization, and reducing the frequency of such events.